The Dual-Process Model Approach in Processing Product Information and Habitual Behavior: Its Impact on Consumer Purchase Intention and the Significance of TikTok Live Streaming Features in Indonesia - Raden Roro Inggil Pratiwi; Nurdin Sobari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the application of the dual-process model in processing product information and habitual behavior, as well as its impact on consumer purchase intention within the context of TikTok Live Streaming commerce in Indonesia. The research explores the significance of live streaming features such as real-time communication, perceived enjoyment, and broadcast competence in shaping consumer behavior. Using a quantitative approach, data were collected from respondents who engage with TikTok Live Streaming for beauty and personal care products. The findings reveal that perceived enjoyment positively influences habit formation, while broadcast competence reduces product uncertainty and enhances purchase intention. These results contribute to the understanding of consumer behavior in digital commerce and provide managerial implications for businesses leveraging live streaming platforms.